PERBANDINGAN METODE ADALINE DAN BACKPROPAGATION DALAM MENENTUKAN JUMLAH INVESTASI UMKM DI KABUPATEN PAMEKASAN - IMANIYAH, MASFUFATUL; YULIANTO, TONY; KUZAIRI, KUZAIRI; YUDISTIRA, IRA; AMALIA, RICA (E-Jurnal Matematika, 2025)
Investment activity is an important factor in developing a business venture. Investment activities carried out generally result from investment decisions that consider various factors. MSME players in general often do not obtain sufficient knowledge and information in determining the amount of investment that must be spent by MSME players. In this case the author compares two methods, namely Backpropagation and Adaline, in determining the amount of investment for MSME players. Both methods have their own advantages and disadvantages. So it cannot be said directly which method is suitable for forecasting, because a method that is good for one case is not necessarily good for a different case. Therefore, the two methods will be compared in determining the amount of MSME investment so that it is known which method has better forecasting accuracy performance. Based on the test results, the Adaline and Backpropagation methods can be implemented to determine the amount of MSME investment. The prediction results using the Backpropagation method are better than using the Adaline method. Where the MSE (Mean Square Error) obtained via the Backpropagation method is 0.0085492 from Training data and from Testing data is 0.0072753, while the Adaline method obtains a value of 2.47E+16.